Hypertrophy of the right ventricle by pulmonary artery banding in rats: a study of structural, functional, and transcriptomics alterations in the right and left ventricles - Silva, Jairo Montemor Augusto; Antonio, Ednei Luiz; Dos Santos, Luis Felipe Neves; Serra, Andrey Jorge; Feliciano, Regiane Santos; Junior, Jose Antonio Silva; Ihara, Silvia Saiuli Miki; Tucci, Paulo Jose Ferreira; Moises, Valdir Ambrosio (Frontiers in Physiology, 2023)
Introduction: Right ventricular remodeling with subsequent functional impairment can occur in some clinical conditions in adults and children. The triggering factors, the molecular mechanisms, and especially the evolution over time are still not well known. Left ventricular (LV) changes associated with right ventricular (RV) remodeling are also poorly understood. Objectives: • To evaluate RV morphological, functional, and gene expression parameters in rats submitted to pulmonary artery banding compared to control rats, with the temporal evolution of these parameters. • To analyze the influence of RV remodeling by pulmonary artery banding in rats and their controls over time on LV geometry, histology, gene expression, and functional performance.